Characterisation of the auxiliary heating power delivered by the 40 keV neutral beam injectors on the COMPASS tokamak. (1st February 2023) - Bogar, K; Varju, J; Havlicek, J; Stockel, J; Podolnik, A; Hron, M; Panek, R
Abstract: Two identical neutral beam injectors (NBIs) have been installed on the COMPASS tokamak. Each of them is capable of producing a deuterium (or hydrogen, helium) neutral beam with nominal power of up to 400 kW at 40 keV. Since the COMPASS tokamak is a compact machine, the design of the neutral beams was carefully optimized to fit the neutral beam through the narrow ports of the tokamak. However, once the neutral beams are operated out of the scope of their optimal parameters, additional power losses occur due to neutral beam scraping. This article investigates the amount of power loss due to neutral beam scraping. The losses are calculated using the neutral beam models and measured neutral beam parameters. The calculated results are compared with the measured power delivered into the plasma. Two different neutral beam models are employed. One describes the neutral beam as a sum of small beamlets, which are Gaussian-like. The second one describes the neutral beam as a single Gaussian beam. The amount of the power lost to scraping is determined by both models and compared. Neutral beam parameters, the input parameters for both models, are derived from the Doppler-shifted spectra emitted by fast neutral atoms. It is shown that when operating NBIs at nominal parameters, the scraping losses are negligible ( < 5% ). If the NBIs are operated too far from the nominal parameters, the scraping losses can reach up to ∼60% of the NBI output power. As the highest fractional losses occur with low power NBI, the beam duct is capable of withstanding the corresponding power loads. The expected auxiliary heating power P A U X, the power entering the tokamak chamber carried by fast neutrals, is benchmarked against the additional plasma input power observed in the measured plasma parameters P N B I . The additional plasma input power P N B I is derived from the plasma power balance . The power balance terms are independent of the neutral beam model used for the auxiliary heating power calculation P A U X . The results of the power balance evaluation reveal a difference between two NBIs installed on COMPASS. One of the injectors systematically delivers 17% less power than the other into the plasma given the same beam parameters. It is concluded that the additional losses occur before the beam enters the tokamak chamber.